The Effect of Three Types of Manure on the Growth of Spinach (Amaranthus sp.). - Susanti, Ambar (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The purpose of this study was to determine the effect of giving three types of manure on the growth of spinach (Amaranthus sp). The research was conducted at the Faculty of Agriculture, University of KH.A. Wahab Hasbullah from December 2022 to March 2023. The material used was pulled spinach seeds (Amaranthus tricolor L.) Panah Merah’s brand is produced by P.T. East West Seed Indonesia, processed organic fertilizer made from cows of Faculty of Agriculture, University of KH.A. Wahab Hasbullah (PK1), goats obtained from P4S Bengkel Mimpi Malang (PK2), and chickens from processed livestock products (PK3). After 30 days of planting, it was found that the addition of manure from three types of ruminant waste had a better effect on plant height, number and leaf area of spinach than the control. Manure as raw material for goat manure had significant plant height (21.25 cm), number of leaves (8.33), and leaf area (3.72 cm2) compared to the other 2 treatments manure and control